IP-10 in Autoimmune Thyroiditis - Ruffilli, I.; Ferrari, S. M.; Colaci, M.; Ferri, C.; Fallahi, P.; Antonelli, A. (Hormone and Metabolic Research, 2014)
The interferon-γ-inducible protein 10 (IP-10) was initially identified as a chemokine that is induced by interferon (IFN)-γ. IP-10 exerts its function through binding to chemokine (C-X-C motif) receptor 3 (CXCR3). IP-10 and its receptor, CXCR3, appear to contribute to the pathogenesis of many autoimmune diseases, organ specific (such as type 1 diabetes, Graves’ disease and ophthalmopathy), or systemic (such as systemic lupus erythematosus, mixed cryoglobulinemia, Sjogren syndrome, or systemic sclerosis). The secretion of IP-10 by (CD)4+, CD8+, and natural killer is dependent on IFN-γ. Under the influence of IFN-γ, IP-10 is secreted by thyrocytes. Determination of high level of IP-10 in peripheral fluids is therefore a marker of a T helper 1 orientated immune response. High levels of circulating IP-10, have been shown in patients with autoimmune thyroiditis (AT). Among patients with AT, IP-10 levels were significantly higher in those with a hypoechoic ultrasonographic pattern, which is a sign of a more severe lympho-monocytic infiltration, and in those with hypothyroidism. For these reasons, it has been postulated that IP-10 could be a marker of a stronger and more aggressive inflammatory response in the thyroid, subsequently leading to thyroid destruction and hypothyroidism. Further studies are needed to investigate whether IP-10 is a novel therapeutic target in AT.
Keywords: thyroid autoimmunity; CXCL10; CXCR3; thyroid autoantibodies